2022
DOI: 10.3389/fpsyg.2022.839629
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Viewers’ Live Streaming Watching: A Perspective of Social Presence Theory

Abstract: Live streaming commerce as a popular marketing method has attracted wide attention, but little is known about why consumers continue to watch live streaming. To fill this research gap, this study draws on social presence theory to examine the impact of sense of community, emotional support, and interactivity on viewers’ social presence, which, in turn, influences their live streaming watching. Furthermore, the moderating role of streamer attractiveness is also investigated. The authors collected survey data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 94 publications
(178 reference statements)
3
27
0
Order By: Relevance
“…It can both improve the conversion rate of both physical and virtual stores, and expose the brand to the public (Xue and Liu, 2022). Previous studies have shown that e-commerce live streaming consumer' purchase intentions can be influenced by live streaming strategy (Zhang et al, 2020), IT affordances (Sun et al, 2019), interaction (Li et al, 2021;Zhang et al, 2021b), and social presence (Ang et al, 2018;Chen and Liao, 2022). However, little research has been devoted to studying the impacts of e-commerce live streaming features on consumer's purchase intention systematically, and there are still very few studies on tourism e-commerce live streaming (Deng et al, 2021;Qiu et al, 2021;Lin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It can both improve the conversion rate of both physical and virtual stores, and expose the brand to the public (Xue and Liu, 2022). Previous studies have shown that e-commerce live streaming consumer' purchase intentions can be influenced by live streaming strategy (Zhang et al, 2020), IT affordances (Sun et al, 2019), interaction (Li et al, 2021;Zhang et al, 2021b), and social presence (Ang et al, 2018;Chen and Liao, 2022). However, little research has been devoted to studying the impacts of e-commerce live streaming features on consumer's purchase intention systematically, and there are still very few studies on tourism e-commerce live streaming (Deng et al, 2021;Qiu et al, 2021;Lin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on online celebrities have mainly focused on (1) trustworthiness, attractiveness, and live streaming content (Wanghong vs. self)-product fit (Park and Lin, 2020 ), (2) online celebrities' image and product consistency (Liu et al, 2020 ), (3) celebrity characteristics (i.e., credibility, professionalism, skill, interaction, and attraction) (Meng et al, 2020 ) on purchase intention. Studies on professional streamers have mainly dedicated to (1) user stickiness affected by technical factors (synchrony and alternative expressions) and social factors (interaction and identification); (2) purchase intention affected by social capital and negative event (Xu et al, 2022 ); consumer engagement (Addo et al, 2021 ), interpersonal factors (perceived expertise, perceived similarity, perceived familiarity and perceived likeability) (Chen et al, 2021 ), crosss-border E-commerce live streaming features (Guo et al, 2021 ); social status (Hou et al, 2020 ), IT affordability (Sun et al, 2019 ); (3) intention to watch influenced by interactivity and top streamers' personal traits (Guo et al, 2022 ); sense of community, interactivity, and emotional support (Chen and Liao, 2022 ); (4) tipping and gift-giving intention affected by audience (Lu et al, 2021 ), live streamers' personal traits (trustworthiness, expertise, attractiveness) and live scene characteristics (telepresence, instant feedback, interactivity, entertainment) (Li and Peng, 2021 ); (5) consumer engagement influenced by interactivity (Kang et al, 2021 ), trust (trust in community members, trust in broadcasters, trust in products) (Guo et al, 2021 ), streamers' emotion (Lin et al, 2021 ), perceived values (Wongkitrungrueng and Assarut, 2020 ), financial bonds, and social bonds structural ties (Hu and Chaudhry, 2020 ), and live interaction (Xue et al, 2020 ). A recent study on celebrity streamers has investigated that interactivity has a positive effect on purchase intention through social presence and flow experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(3) intention to watch influenced by interactivity and top streamers' personal traits (Guo et al, 2022); sense of community, interactivity, and emotional support (Chen and Liao, 2022); (4) tipping and gift-giving intention affected by audience (Lu et al, 2021), live streamers' personal traits (trustworthiness, expertise, attractiveness) and live scene characteristics (telepresence, instant feedback, interactivity, entertainment) (Li and Peng, 2021); (5) consumer engagement influenced by interactivity (Kang et al, 2021), trust (trust in community members, trust in broadcasters, trust in products) (Guo et al, 2021), streamers' emotion (Lin et al, 2021), perceived values (Wongkitrungrueng and Assarut, 2020), financial bonds, and social bonds structural ties (Hu and Chaudhry, 2020), and live interaction (Xue et al, 2020). A recent study on celebrity streamers has investigated that interactivity has a positive effect on purchase intention through social presence and flow experience.…”
Section: ) Studies On Online Celebrities Have Mainly Focused Onmentioning
confidence: 99%
“…Furthermore, Lo et al (2022) revealed that parasocial interaction contributes to consumers' affective reactions, leading to their impulsive buying behaviors. Especially during COVID-19 containments, consumers' purchase intention was influenced by their feelings of loneliness and boredom (Peng et al, 2022;Zuo et al, 2022a), and live commerce provided emotional support and social presence (Chen and Liao, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although streamer attractiveness was found to play a significantly moderating role between consumers' social presence and live streaming engagement (Pan et al, 2021;Chen and Liao, 2022) regarded homogenization of live content as one of the existing problems of live streaming commerce. Extant studies suggested that streamer genre (Zhang et al, 2022a), entertainment perception (Chen et al, 2020a), and information credibility (Wang et al, 2022) can facilitate streamers to implement differentiated competition strategies.…”
Section: Introductionmentioning
confidence: 99%